UNIVERSITY LEVEL TEACHING STYLES WITH HIGH SCHOOL STUDENTS AND INTERNATIONAL TEACHING AND LEARNING - Radin, Michael Alexander; Orlova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The main aim of this paper is to render how university level courses are taught in high school. In fact, we will focus on what styles are used to teach university level courses and illustrate the international contrasts that happen quite frequently. In addition, we will analyse the details of teaching styles that were implemented in the American and the Latvian educational systems. Furthermore, we will discuss what specific teaching styles and innovations work successfully, and what teaching styles and innovations had difficulties and need improvements. In particular, implementing the hands-on teaching and learning styles and repetitive type teaching and learning styles. Moreover, we will also discuss the risk involved with introducing and transforming university level courses and teaching styles with high school students and how to manage these risks.